Time for integration: communication in the immune system - Vitale, Marco (Acta Biomedica Atenei Parmensis, 2007)
Signals exchanged between cells in the immune system are generated at specific contact regions termed “immunological synapses” (IS). The morphology and the functions of IS vary with circumstances and include directing secretion and integrating positive and negative signals to tune the extent of response – a model that is essentially derived from neurosciences. Indeed, the mechanisms of signal integration and antigen decoding are not yet completely understood and many hypotheses are worked out.